(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Water contamination by herbicides and chelating agents is increasing mainly due to theÂ increasing agricultural activities. Water contamination by these compounds has become aÂ concern due to their adverse effects to the environment and humans. Seven sampling sites ofÂ water sources in Selangor and Johor were chosen for the study. Contamination level ofÂ Mecoprop (MCCP), Nitrilotriacetic acid (NTA) and Ethylenediaminetetraacetic acid (EDTA) inÂ these water body areas was determined by using Gas Chromatography-Electron CaptureÂ Detector (GC-ECD). Our results indicated that water samples of Sungai Melot in SelangorÂ showed the highest presence of EDTA. MCCP was detected at a high level at Sungai SarangÂ Buaya, Johor while NTA showed similar level of concentration at three different sites, LadangÂ 10, Ladang Sayur and Mardi, Selangor